X-Ray Structure Reveals a New Class and Provides Insight into Evolution of Alkaline Phosphatases - Bihani, Subhash C. (Public Library of Science, 2011)
The alkaline phosphatase (AP) is a bi-metalloenzyme of potential applications in biotechnology and bioremediation, in which phosphate monoesters are nonspecifically hydrolysed under alkaline conditions to yield inorganic phosphate. The hydrolysis occurs through an enzyme intermediate in which the catalytic residue is phosphorylated. The reaction, which also requires a third metal ion, is proposed to proceed through a mechanism of in-line displacement involving a trigonal bipyramidal transition state. Stabilizing the transition state by bidentate hydrogen bonding has been suggested to be the reason for conservation of an arginine residue in the active site. We report here the first crystal structure of alkaline phosphatase purified from the bacterium Sphingomonas. sp. Strain BSAR-1 (SPAP). The crystal structure reveals many differences from other APs: 1) the catalytic residue is a threonine instead of serine, 2) there is no third metal ion binding pocket, and 3) the arginine residue forming bidentate hydrogen bonding is deleted in SPAP. A lysine and an aspargine residue, recruited together for the first time into the active site, bind the substrate phosphoryl group in a manner not observed before in any other AP. These and other structural features suggest that SPAP represents a new class of APs. Because of its direct contact with the substrate phosphoryl group, the lysine residue is proposed to play a significant role in catalysis. The structure is consistent with a mechanism of in-line displacement via a trigonal bipyramidal transition state. The structure provides important insights into evolutionary relationships between members of AP superfamily.